Леся Українка на шпальтах південноукраїнських альманахів: творчий дебют - Лубчак, Вадим; Lubchak, Vadуm (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто особливості упорядкування та видання південноукра- їнських літературних альманахів кін. ХІХ – поч. ХХ ст., зокрема акцентовано увагу на представленій у збірниках «З-над хмар і з долин» (Одеса, 1903) та «З потоку життя» (Херсон, 1905) творчості Лесі Українки. Досліджено історію співпраці Лесі Українки з редакторами альманахів, наведено оцінку реакції тогочасної критики на творчий дебют авторки в цих збірниках. The article considers the features of compiling and publication of South Ukrainian literary almanacs in the late 19 − early 20th century. Special attention is focused on Ukrainka’s works in anthologies “Z-nad khmar i dolyn” (“From the clouds and valleys”) (Odesa, 1903) and “Z poyoku zhyttya” (“From the life’s stream”) (Kherson, 1905). Author examines the history of cooperation between writer and editors of almanacs, evaluates the reaction of contemporary criticism on her debut. Although in the early 20th century writer’s works were published in the Russian part of Ukraine (she cooperated with Russian journal Zhyzn’ “Life”, placed her poems in anthologies, including literary and artistic one “Skladka” (“Crease”) (Kharkiv, 1896)), her name wasn’t know well by the readers of South of Ukraine. The study analyzes form of cooperation between Lesіa Ukrainka and compilers of almanacs, Mykola Voronyi, Mykhailo Kotsyubynskyi and Mykola Chernyavskyi. Special attention is focused on conformity of author’s artistic and aesthetic concepts for anthologies “Z-nad khmar i dolyn” and “Z potoku zhyttya”.
Lesіa Ukrainka on the Pages of South Ukrainian Almanacs: Creative Debut
Keywords: літературний альманах; автор; цензура; символ; орієнтир; видавець; literary almanac; author; publisher; censorship; symbol; guide